A comprehensive review of emerging contaminants in water sources - Abdulmumin Muhammad , Ma’aruf; Muhd Shafi’i , Abubakar; Musa Shuaibu , Abubakar; Usman Alhaji , Usman; Rabilu Abdullahi , Sabiu; Abdurrashid , Ibrahim (International Journal of Advanced Chemistry, 2024)
The quality of water is crucial for the health of both the environment and humans, but new challenges from emerging contaminants threaten this vital resource. This paper reviews the origin and significance of water quality issues linked to emerging pollutants, including pharmaceuticals, personal care products, endocrine-disrupting chemicals, per- and polyfluoroalkyl substances, microplastics, pesticides, and industrial chemicals. These persistent chemicals exhibit complex behaviors and have the potential to impact ecological systems and human health significantly. The review comprehensively examines the pathways through which these pollutants enter water systems, such as agricultural runoff, industrial discharges, and urban stormwater runoff. It also covers the latest techniques for identifying these pollutants, emphasizing recent advancements in sampling methods and analytical techniques while highlighting the challenges of detecting contaminants at low concentrations. The discussion includes the environmental behavior of these contaminants, focusing on their properties, degradation mechanisms, and bioaccumulation potential. It further explores the impacts of these emerging contaminants on ecosystems and human health, examining both conventional and innovative treatment technologies. Additionally, the review identifies current research gaps and future trends in the analysis of new pollutants. It underscores the importance of public awareness, effective communication strategies, and innovative approaches to environmental protection.